Adaptation of mesoscale turbulence parameterisation schemes as RANS closures for ABL simulations. Issue 10 (2nd October 2016) - Temel, O.; van Beeck, J.
ABSTRACT: The present study presents different k-ε turbulence closures for atmospheric boundary layer flows using computational fluid dynamics (CFD) simulations that are consistent with inflow conditions from numerical weather prediction (NWP) simulations. Eight different mesoscale turbulence parameterisation schemes of the Weather Research and Forecasting (WRF) model are covered. To ensure consistency between the NWP and CFD simulations, different closure coefficients of the k − ε turbulence model for each NWP scheme are proposed. This is achieved by combining production–dissipation closure coefficient relationships based on the Monin–Obukhov similarity theory and the formulation based on the Coriolis parameter proposed by Detering and Etling. The proposed methodology has been implemented in the open source CFD toolbox OpenFOAM and is demonstrated at near-neutral stability conditions for the classical Askervein Hill case.